THE CONTRIBUTION OF FEMALE COMMUNICATION TO THE DEVELOPMENT OF FAMILY SOCIO-ECONOMIC RESILIENCE IN BANDUNG WETAN MSMES - Alin Yulianti; Pupi Indriati Zaealani; Ahmad Muzakki (TOPLAMA, 2026)
This research aims to examine the role of communication among women entrepreneurs in MSMEs in Bandung Wetan in building the socio-economic resilience of families. Women have a dual role as business drivers and household economic supporters. The communication strategies they use, both in the family environment and in business activities, become important factors in maintaining business continuity and family welfare. This research uses a qualitative approach with a case study method on women's MSME groups in Bandung Wetan. Data were collected through in-depth interviews, observations, and documentation. The research results show that effective communication among family members, communication with customers, and the use of digital media are the main assets for women in SMEs in facing socio-economic challenges. In addition, social support from family also strengthens the resilience of their businesses. These findings are expected to contribute to strengthening the communication capacity of women entrepreneurs and serve as a consideration in designing family-based MSME empowerment programs.